Energy Management Strategies for Optimal Hybrid Microgrid Configuration in the Smart Village Context - Fakhar, Adila (Universiti Malaysia Sarawak (UNIMAS), 2018)
Most of the rural areas in Sarawak, particularly the remotest villages are not connected to the power grid. Integrating the local Renewable Energy Resources (RER) in these remote areas with certain capacities of energy storage and diesel generators in the form of hybrid generating system can be utilized to meet the growing need of electricity. However, the use of diesel generators as a backup is costly and environmentally troublesome. On the other hand, electrification of these areas is a daunting task and needs huge investment as it is difficult connecting them to the main power grid. On the same note, relying heavily on the battery during off-peak PV generation results in battery lifetime decrement which in turn increases the cost of energy (COE). Nowadays, the main issue is the random installation of RER without bearing in mind the optimal configuration. Furthermore, utilizing natural resources that form islanded microgrids located in different areas can pose peculiar energy management issues, when different energy providers manage the renewable and non-renewable small powerhouses. To address the above mentioned problems, a framework of an optimal standalone hybrid renewable energy system is proposed, which is the first instance of techno-economic analysis performed with a dynamic validation. The best configuration of the system is firstly selected by sensitively analyzing different microgrid models in terms of electricity price, initial capital cost, operating cost, carbon dioxide (CO2) emission reduction and the net present cost (NPC). In the next stage, an operational analysis has been applied to ensure the reliability and security of the system. Further, the framework has been extended to focus on an existing hybrid renewable design for minimizing the operating time of diesel generators and increasing the battery lifetime, taking into account the uncertainty of solar Photovoltaic (PV) power. With these aims, an effective power dispatch algorithm has been developed for clustered microgrids incorporating power sharing control using Power Line Communication (PLC). A part of the developed algorithm is used to deal with the optimal scheduling control while the other actuates the dynamic demand response based PV power forecasting. The performances of the proposed approaches with the formulated Backup Injection Index (BII) have been validated using two test systems from “Long San Village in Sarawak” and “Bario, Sarawak”. The initial studies of optimal economic analysis were carried out using the Hybrid Optimization Model for Electric Renewable (HOMER), while the operational analysis utilizing the Power System Computer Aided Design (PSCAD). The hybrid energy management algorithm-based the PLC signal was developed using the MATLAB. The results show that the optimal configuration with the lowest COE and NPC can be achieved if the installed solar PV is less than 61 kW with 85 kWh of energy storage and 11 kW of hydro generation. The dynamic analysis shows that in order to reduce the voltage drop during disturbances, it is crucial to carefully install the sources in the buses with the highest load demand. The usefulness of the proposed hybrid energy management system is more obviously indicated by the low usage of backup power from battery banks and diesel generators for 24 hours. For instance, in the current operation, the hybrid system requires 814 kW backup power from diesel, whereas this value reduces to 675 kW when analytical method is used. In the proposed hybrid energy management, the backup power needed is only 176 kW. It was also found that the frequency shift keying technique is capable to transfer the switching command with a minimum delay compared with other techniques. Keywords: Rural communities in Sarawak, standalone microgrids, energy storage, techno-economic studies, operational analysis, intelligent hybrid management system, power-line communication signal.